Adsorption of Ar and N[2] on Dealuminated Mordenite Tuffs; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Ortega K. Karla; Hernandez M. A. Miguel Angel; Portillo R. Roberto; Ayala E. Edgar; Romero Omar; Rojas F. Fernando; Rubio E. Efrain; Pestryakov A. N. Aleksey Nikolaevich; Petranovskii V. Vitalii (2015, 2015)
Title screen